Detection of spontaneous preterm birth by maternal urinary volatile organic compound analysis: A prospective cohort study - Ronde, Emma; Frerichs, Nina M.; Brantenaar, Shauni; El Manouni El Hassani, Sofia; Wicaksono, Alfian N.; Covington, James A.; De Boer, Nanne K. H.; De Meij, Tim G.; Hankemeier, Thomas; Reiss, Irwin K. M.; Schoenmakers, Sam (Frontiers in Pediatrics, 2022)
Accurate prediction of preterm birth is currently challenging, resulting in unnecessary maternal hospital admittance and fetal overexposure to antenatal corticosteroids. Novel biomarkers like volatile organic compounds (VOCs) hold potential for predictive, bed-side clinical applicability. In a proof of principle study, we aimed to assess the predictive potential of urinary volatile organic compounds in the identification of pregnant women at risk for preterm birth. Urine samples of women with a high risk for preterm birth (≧ 24+0 until 36+6 weeks) were collected prospectively and analyzed for VOCs using gas chromatography coupled with an ion mobility spectrometer (GS-IMS). Urinary VOCs of women delivering preterm were compared with urine samples of women with suspicion of preterm birth collected at the same gestation period but delivering at term. Additionally, the results were also interpreted in combination with patient characteristics, such as physical examination at admission, microbial cultures, and placental pathology. In our cohort, we found that urinary VOCs of women admitted for imminent preterm birth were not significantly different in the overall group of women delivering preterm versus term. However, urinary VOCs of women admitted for imminent preterm birth and delivering between 28+0 until 36+6 weeks compared to women with a high risk for preterm birth during the same gestation period and eventually delivering at term (>37+0 weeks) differed significantly (area under the curve: 0.70). In addition, based on the same urinary VOCs, we could identify women with a confirmed chorioamnionitis (area under the curve: 0.72) and urinary tract infection (area under the curve: 0.97). In conclusion, urinary VOCs hold potential for non-invasive, bedside prediction of preterm birth and on the spot identification of intra-uterine infection and urinary tract infections. We suggest these observations are further explored in larger populations.